In Vitro-In Vivo Correlations (IVIVC) for Predicting the Clinical Performance of Metronidazole Topical Creams Intended for Local Action - Seeprarani Rath; Isadore Kanfer (MDPI AG, 2023)
The safety and efficacy of a generic medicine can be confirmed by demonstrating bioequivalence (BE) between the generic product and its reference listed drug (RLD) by measuring drug concentrations in the blood following administration. However, for topical dermatological products that are not absorbed into the systemic circulation, clinical trials in patients are required. The objective of this investigation was to use an in vitro method to predict in vivo performance by correlating in vitro release testing (IVRT) data with tape stripping (TS) data following the application of metronidazole (MTZ) creams to the skin of healthy human participants. Whereas IVRT is generally used to characterize the release of a drug from topical products across a synthetic membrane into a suitable receptor medium, TS involves the sequential removal of layers of stratum corneum (SC) with an adhesive tape to determine the amount of the drug in the skin. The resulting IVRT and TS data were correlated using the IVRT parameter of the apparent release constant (ARC), which is the slope obtained from the release rate profile, with the TS parameter of the area under the curve (AUC) obtained from a plot of the amount of drug per tape strip vs. the relative SC depth. A rank order relationship for these parameters was established for the reference and test products. A graph of AUC vs. ARC was plotted to establish a Level C in vitro-in vivo correlation (IVIVC). Although the ARC for T1 was slightly lower than that for the reference, the rank order was essentially consistent. A linear relationship was observed between the AUCs and ARCs. The equation derived was used to predict the AUCs for all the tested products based on their respective ARCs. The predicted AUC values based on the observed ARCs were similar to the observed AUCs. The lower and upper limits for the in vitro and in vivo parameters for BE were computed based on regulatory acceptance criteria. In order to predict BE from the IVRT studies, the values of the ARC should be between 30.50 and 47.67 when comparing test and reference cream products containing MTZ.